Genomic Determinants of Pathogenicity and Antimicrobial Resistance for 60 Global Listeria monocytogenes Isolates Responsible for Invasive Infections - Shi, Dawei; Anwar, Tanveer Muhammad; Pan, Hang; Chai, Wenqin; Xu, Sihong; Yue, Min (Frontiers in Cellular and Infection Microbiology, 2021)
Listeria monocytogenes remains a significant public health threat, causing invasive listeriosis manifested as septicemia, meningitis, and abortion with up to 30% of cases being the fatal outcome. Tracking the spread of invasive listeriosis requires updated knowledge of virulence factors (VFs) and antimicrobial resistance features, which is an essential step towards its clinical diagnosis and treatment. Taking the advantage of high-throughput genomic sequencing, we proposed that the differential genes based on the patho-genomic composition could be used to evaluate clinical observations and therapeutic options for listeriosis. Here, we performed the comparative genomic analysis of 60 strains from five continents with a diverse range of sources, representing serotypes 1/2a, 1/2b, 1/2c, and 4b, comprising of lineage I and lineage II and including newly contributed 13 Chinese isolates from clinical cases. These strains were associated with globally distributed clonal groups linked with confirmed foodborne listeriosis outbreaks and sporadic cases. We found that Listeria monocytogenes strains from clonal complex CC8, CC7, CC9, and CC415 carried most of the adherence and invasive genes. Conversely, CC1, CC2, CC4, CC6 with the least number of adherence and invasive genes. Additionally, Listeria pathogenicity islands-1 (LIPI-1), LIPI-2, intracellular survival, surface anchoring, and bile salt resistance genes were detected in all isolates. Importantly, LIPI-3 genes were harbored in CC3, CC224, and ST619 of Chinese isolates, and in CC1, CC4, and CC6 of other worldwide isolates. Notably, Chinese isolates belonged to CC14 carried antibiotic resistance genes (ARGs) against β-lactams (blaTEM-101, blaTEM-105) and macrolide (ermC-15) whereas CC7 and CC8 isolate harbored ARGs against aminoglycoside (aadA10_2, aadA6_1) which may pose a threat to therapeutic efficacy. Phylogenomic analysis showed that CC8, CC7 and CC5 of Chinese isolates, CC8 (Swiss and Italian isolates), CC5 and CC7 (Canadian isolates) are closely clustered together besides the same clonal complex. Additionally, CC381 and CC29 of Chinese isolates shared the same genomic pattern as CC26 of Swiss isolate and CC37 of Canadian isolate respectively, indicating strong phylogenomic relation between these isolates. Collectively, this study highlights considerable clonal diversity with well-recognized virulence and antimicrobial-resistant determinants among Chinese and worldwide isolates which stress to design and improved strategies for clinical therapies.